Overview of cosmetic regulation : proceedings of a seminar held on 20th February, 2002 at Sheraton Hotel, Subang - Cosmetic Seminar (2002 : Subang); Malaysia Biro Pengawalan Farmaseutikal Kebangsaan (Subang : BPFK, 2002)
01